A novel archaeal alanine dehydrogenase homologous to ornithine cyclodeaminase and mu-crystallin - Schröder, Imke; Vadas, Alexander; Johnson, Eric; Lim, Sierin; Monbouquette, Harold G (Journal of bacteriology, 2004)
A novel alanine dehydrogenase (AlaDH) showing no significant amino acid sequence homology with previously known bacterial AlaDHs was purified to homogeneity from the soluble fraction of the hyperthermophilic archaeon Archaeoglobus fulgidus. AlaDH catalyzed the reversible, NAD+-dependent deamination of L-alanine to pyruvate and NH4+. NADP(H) did not serve as a coenzyme. The enzyme is a homodimer of 35 kDa per subunit. The Km values for L-alanine, NAD+, pyruvate, NADH, and NH4+ were estimated at 0.71, 0.60, 0.16, 0.02, and 17.3 mM, respectively. The A. fulgidus enzyme exhibited its highest activity at about 82 degrees C (203 U/mg for reductive amination of pyruvate) yet still retained 30% of its maximum activity at 25 degrees C. The thermostability of A. fulgidus AlaDH was increased by more than 10-fold by 1.5 M KCl to a half-life of 55 h at 90 degrees C. At 25 degrees C in the presence of this salt solution, the enzyme was approximately 100% stable for more than 3 months. Closely related A. fulgidus AlaDH homologues were found in other archaea. On the basis of its amino acid sequence, A. fulgidus AlaDH is a member of the ornithine cyclodeaminase-mu-crystallin family of enzymes. Similar to the mu-crystallins, A. fulgidus AlaDH did not exhibit any ornithine cyclodeaminase activity. The recombinant human mu-crystallin was assayed for AlaDH activity, but no activity was detected. The novel A. fulgidus gene encoding AlaDH, AF1665, is designated ala.